Implementasi Metode SAW Dalam Penerimaan Siswa Baru Pada SMA Negeri 16 Medan - Adil Setiawan (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2017)
Acceptance of new students In public schools has always been the number 1 attraction, because the quality of a school is influenced by several things, one of which is the value of prestige against an unstoppable modernization, and one other due to the high accreditation value, as well as the source Competent teaching power. But in this case, to have a quality student resources it is necessary to select the acceptance of students. Similarly, for SMA Negeri 16 Medan which is one of the favorite state high school in marelan area, which is one area in the city of field. In fact quite a lot of prospective students who enroll in SMA Negeri 16 Medan who have high school grades, because the number of prospective students who register exceeds the capacity, the selection of student acceptance based on rankings SMP report cards, and written test only. From the existing problems sometimes there are prospective students who were excluded because they get enough test score when he has a non-academic achievement, and a good personality. Criteria other than academic value, and such as personality and non-academic values, should be used as criteria as well as to determine which students are truly eligible to receive using the SAW method. Non academic is an achievement beyond the academic field that a student has ever achieved. Interview test is an assessment of the personality of the prospective student will be in by the enrollment system. This SAW method serves as a tool of SMA Negeri 16 Medan in making decisions on the selection process of new admissions.